Examining family engagement practices: a rural middle school case study - Mauk, Kimberly (My University, 2024)
The purpose of this study was to examine family engagement practices in a rural Midwestern middle school. Grounded in the National PTA Standards for Family-School Partnerships as a conceptual framework and utilizing the Comprehensive Rural Wealth Framework as a theoretical foundation, the study explored family engagement resources, student growth in the areas of academic, social-emotional, and general well-being, and meaningful communication with families. Using a qualitative case study design, the research employed interviews and focus groups with teachers, administrators, and parents to gather insights into their perceptions of family engagement. The significance of this study lies in its potential to reveal strategies that enhance family-school collaboration in rural settings, where resources and technological barriers pose unique challenges. The investigation utilized a combination of individual interviews and focus groups to gather data on family engagement practices. The study identified key themes such as communication challenges, technology barriers, cultural inclusivity, and community partnerships. The findings underscore the importance of building robust communication infrastructures and culturally sensitive practices to foster meaningful family engagement in rural areas. The use of digital platforms has grown, but challenges remain, especially for non-English-speaking families, highlighting the need for ongoing adjustments to communication methods. The study's findings revealed that family engagement has evolved into a more collaborative partnership, significantly impacting student academic outcomes and well-being. The behaviors and strategies employed by teachers and administrators, such as differentiated instruction, cultural sensitivity, and community involvement, were instrumental in supporting student success. Recommendations for future research include a deeper exploration of tailored family engagement strategies for rural communities, with a focus on overcoming technological and linguistic barriers. These findings have significant implications for practice, as they highlight the necessity of flexible and inclusive family-school partnerships that can adapt to the unique needs of rural middle schools.
Keywords: Engagement; Family engagement; Best practices; Family involvement